proBDNF expression induces apoptosis and inhibits synaptic regeneration by regulating the RhoA-JNK pathway in an in vitro post-stroke depression model - Bangkun Yang (Nature Publishing Group, 2021)
Abstract Brain-derived neurotrophic factor (BDNF) plays an important role in the pathophysiology of post-stroke depression (PSD). However, the precise function and potential mechanism of proBDNF, the precursor form of BDNF, are unknown. In our study, a PSD-like model was established by treating neuronal cells with oxygen-glucose deprivation and corticosterone. We found that the protein proBDNF levels were significantly higher in the cortex and hippocampus in the PSD group than in the control group, suggesting that proBDNF plays a role in the pathophysiology of PSD. Furthermore, we re-established the PSD-like cell model using recombinant p75 neurotrophin receptor (p75NTR) or silencing c-Jun N-terminal kinase (JNK), and found that the PSD-induced upregulation of proBDNF was inhibited by recombinant p75NTR and JNK silencing (siJNK), and increased cellular apoptosis. Moreover, the application of recombinant p75NTR and siJNK in the PSD-like cell model significantly reversed the expression of apoptosis-related and depression-related proteins and decreased cellular apoptosis. Our findings suggest that proBDNF is involved in neural plasticity in PSD in vitro. The RhoA-JNK signaling pathway is activated after proBDNF binds to the p75NTR receptor, followed by the expression of apoptosis-related proteins (PSD95, synaptophysin, and P-cofilin), which contribute to PSD progression. The mechanism might involve the promotion of cellular apoptosis and the inhibition of nerve synapses regeneration by proBDNF.